The Impact of Corporate Governance on Nepalese Commercial Banks’ Financial Performance - Goet, Joginder (Journal of Management, 2022)
This research examines the impact of many bank-specific characteristics on the financial performance of listed commercial banks in Nepal, including board size, firm size, foreign ownership, and credit to deposit ratio. The panel data (70 observations) of 7 listed banks out of 27 banks was used to examine the determinants of banks’ financial performance, such as ROE. The relationship and effect of the above-mentioned factors on the financial performance of commercial banks in Nepal were investigated using a correlational and causal research methodology in this study. This research discovered a link between board size, business size, foreign ownership, and credit-to-deposit ratio with financial performance. Again, the size of the board of directors, the size of the company, foreign ownership, and the credit-to-deposit ratio have all been found to have a major influence on financial success.